The Reality of Communication Among Adherents Different Religion: Chinese and Serang Javanese Ethnicity - Mega Febrianti; Nurbaiti Arifiana; Zaenal Mukarom (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2022)
In many studies, religion is often seen as the most mysterious domain because it often confronts, even contradicts a number of rational arguments. Religion is often used as a media for debate regarding problems that occur, especially between adherents of different religions. Matters related to religion are very sensitive. The reality of communication that is faced is also sometimes different, depending on the ethnicity, culture and religion behind it. Researchers want to know the reality of communication between adherents of different religions between the Chinese and Javanese Serang ethnicities in the old Banten area. In addition, to find out the communication management of religious leaders and the communication patterns developed. The research method used by researchers in carrying out this research is qualitative research with a descriptive approach and adheres to the constructivism paradigm. The results of the study show that the reality of communication between adherents of different religions is very good, intercultural communication patterns occur when deliberations and mutual cooperation activities are carried out in Kp. Pamarican which is used as a meeting place and carries out various activities in the environment, the people of Kp. Pamarican is able to carry out the process of integration and accommodation by providing space to live and fulfilling basic rights for Chinese residents providing opportunities to carry out distinctive cultural activities such as Chinese New Year celebrations and other holidays. Keywords: Chinese, Serang Javanese, ethnicity, religion, multiculturalism Abstrak Dalam banyak kajian, agama seringkali dipandang sebagai domain paling misterius karena seringkali berhadapan, bahkan bertentangan dengan sejumlah argumentasi rasional. Agama seringkali dijadikan media perdebatan terkait problematika yang terjadi khususnya diantara pemeluk agama yang berbeda. Hal-hal yang berkaitan dengan agama, sifatnya sangat sensitif. Realitas komunikasi yang dihadapi juga terkadang berbeda, tergantung suku budaya dan agama yang melatar belakanginya. Peneliti ingin mengetahui realitas komunikasi pada penganut beda agama antara etnis tionghoa dan jawa serang di kawasan banten lama. Selain itu, untuk mengetahui manajemen komunikasi pemuka agama dan pola komunikasi yang di kembangkan. Metode Penelitian yang digunakan oleh penelitian dalam melaksanakan penelitian ini adalah penelitian kualitatif dengan pendekatan deskriptif dan menganut paradigma konstruktivisme. Hasil penelitian menunjukkan bahwa realitas komunikasi di antara penganut umat beda agama sangat baik, pola komunikasi antar budaya terjadi ketika kegiatan musyawarah dan kegiatan gotong royong yang dilakukan di Kp. Pamarican yang dijadikan sebagai tempat pertemuan dan melakukan berbagai kegiatan di lingkungan tersebut, masyarakat Kp. Pamarican mampu menjalankan proses integrasi maupun akomodasi dengan menyediakan ruang untuk hidup serta pemenuhan hak-hak mendasar bagi para penduduk Tionghoa memberikan kesempatan untuk menjalankan aktivitas kultural khas seperti perayaan Imlek dan hari-hari besar lainnya. Kata kunci: Chinese, Serang Javanese, ethnicity, religion, multiculturalism